Depressive symptomatology in severe dementia in a European sample: prevalence, associated factors and prescription rate of antidepressants. (11th December 2014) - Giebel, Clarissa M.; Sutcliffe, Caroline; Renom-Guiteras, Anna; Arve, Seija; Hallberg, Ingalill Rahm; Soto, Maria; Zabalegui, Adelaida; Hamers, Jan; Saks, Kai; Challis, David
ABSTRACT: Background: Depression is a common comorbid disorder of dementia. This study explores the prevalence of and factors associated with depressive symptomatology, and antidepressant prescription rates in severe dementia across eight European countries. Methods: In total, 414 people with severe dementia completed measures of cognition and quality of life (QoL), whilst carers completed proxy measures of activities of daily living (ADLs), depression, neuropsychiatric symptoms, QoL and comorbidity. Results: Findings indicated that 30% of the sample had depression, whilst the highest and lowest prevalence of depression was reported in Germany and Finland, respectively. Lower QoL, the presence of pain and more frequent neuropsychiatric symptoms were associated with depressive symptomatology, whilst no significant relationship between impairment of ADLs, comorbidity, and depression emerged. Spain and Estonia had the highest and lowest rates of antidepressant prescribing, respectively, whilst Germany had the highest discrepancy between depressive symptomatology and prescription. Conclusions: The study highlights variations across countries in the prevalence of depressive symptomatology in severe dementia and prescription of antidepressants. Information about factors associated with depressive symptomatology may help to better identify and manage depression.